Nonsmooth continuous-time optimization problems: Sufficient conditions - Rojas-Medar, M. A.; Brandao, AJV; Silva, Geraldo Nunes [UNESP] (Academic Press Inc., 1998)
We discuss sufficient conditions of optimality for nonsmooth continuous-time nonlinear optimization problems under generalized convexity assumptions. These include both first-order and second-order criteria. (C) 1998 Academic Press.